THE EFFECT OF PROGESTERONE INTRAVAGINAL DEVICE AND GONADOTROPIN RELEASING HORMONE ON FERTILITY IN POSTPARTUM DAIRY COWS - I Gusti NP Widyana; Sri Hartantyo; Yanober Mberato (Jurnal Sain Veteriner, 2003)
ABSTRACT The study was carried out to determine the effect of progesterone intravaginal devices and gonadotropin releasing hormone on fertility in postpartum dairy cows. Thirty two postpartum dairy cows having body condition score 3 – 4 were used in this study. The cows were devided randomly into 4 groups. Group I (CIDR 9 d), lI (CIDR 9 d + GnRH), DI (CIDR 15 (1), and IV (CIDR 15 d + GnRH). The GnRH was given at the time of insemination. The result of this study showed that the retention of CIDR devices and estrous induction was 100%. Estrous induction recorded on groups I, 11, BI and IV were 49.50 ± 1.51 ; 49.25 ± 1.67 ; 48.75 ± 1.28 ; 48.25 ± 1.04 hours, respectively. The pregnancy rate on groups I, II, III, and IV were 62.5 % ; 75.0 % 50.0 % ; 62.5 % respectively, no significantly different between groups (P>0.05). However, the mean milk progesterone concentration which take on day 7 of group II, had significantly higher (P< 0.05) than the other groups. It can be concluded that progesterone intravaginal devices and administration of GnRH at the time of AI could be used for induction of estrous and ovulation in dairy cows. Key word: Progesterone, GnRH, Fertility, Postpasrtum Dairy Cows